2015
DOI: 10.1039/c4cc09799h
|View full text |Cite
|
Sign up to set email alerts
|

Indium-catalyzed, novel route to β,β-disubstituted indanones via tandem Nakamura addition–hydroarylation–decarboxylation sequence

Abstract: A novel method for the construction of β,β-disubstituted indanones has been developed via tandem Nakamura addition-hydroarylation-decarboxylation process. Indium(III) triflate was demonstrated as a versatile multitasking catalyst, which catalyzes three different chemical transformations under one-pot conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…An alternative to palladium catalysts was recently disclosed by Prajapati et al who showed that carbocycles can also be easily accessed using an auto‐tandem catalysis approach. For example, a novel indium mediated ATC process for the synthesis of indanones 79 was developed (Scheme ) . In their method, an indium species catalysed both the intermolecular Nakamura reaction between 1,3‐dicarbonyls 76 and phenyl acetylenes 77 to give enones 78 as well as the subsequent hydroarylation and decarboxylation processes.…”
Section: Auto‐tandem Catalysis Approaches To Carbocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to palladium catalysts was recently disclosed by Prajapati et al who showed that carbocycles can also be easily accessed using an auto‐tandem catalysis approach. For example, a novel indium mediated ATC process for the synthesis of indanones 79 was developed (Scheme ) . In their method, an indium species catalysed both the intermolecular Nakamura reaction between 1,3‐dicarbonyls 76 and phenyl acetylenes 77 to give enones 78 as well as the subsequent hydroarylation and decarboxylation processes.…”
Section: Auto‐tandem Catalysis Approaches To Carbocyclesmentioning
confidence: 99%
“…For example, a novel indium mediated ATC process for the synthesis of indanones 79 was developed (Scheme 18). [51] In their method, an indium species catalysed both the intermolecular Nakamura reaction [52] between 1,3-dicarbonyls 76 and phenyl acetylenes 77 to give enones 78 as well as the subsequent hydroarylation and decarboxylation processes. The result of these multiply transformation in a single reactor is the formation of substituted indanones 79 in poor-to-good yields.…”
Section: -Membered Carbocyclesmentioning
confidence: 99%
“…In 2015, Rajesh and Prajapati devised a new route to β,β‐disubstituted indanones 49 employing ethyl aryl benzoate (β‐ketoester) 48 and terminal alkyne 23 using In(OTf) 3 as mild catalyst [44] . The reaction proceeds through tandem Nakamura addition/hydroarylation/decarboxylation sequence under one‐pot condition in refluxing toluene.…”
Section: Acid‐catalyzed Synthesismentioning
confidence: 99%
“…In 2003, Nakamura and co-workers documented an indiumcatalyzed addition of 1,3-dicarbonyl compounds to unactivated 1-alkynes 23 , providing an e cient synthetic route to form 2-alkenyl-1,3-dicarbonyl compounds from abundant carbon alkynes sources. After that, In(III) [24][25][26][27][28] , Re(I) [29][30][31] , Ir(I) 32 , Pd(0) 33 , Co(II) 34 , Mn(I) [35][36] , Ru(I)-(III) 37-39 catalytic systems were discovered, all of which were racemic reports except only one example using substrates with chiral auxiliary 40 . All the above reports, the dicarbonyl compounds and alkynes need to be activated simultaneously.…”
Section: Introductionmentioning
confidence: 99%